Experimental Modelling of the Influence of Boundary Conditions on Kinematics of the Extrusion Process - SKORULSKI, G. (Engineering Transactions, 2005)
The aim of this paper is to analyses the influence of boundary conditions on plastic flow kinematics during hot extrusion of aluminium alloys. Clay and plasticine have been used as a substitute material. The shape and distribution of a dead zone, conditions of increasing the boundary layers and their influence on flow kinematics have been done using the modelling experiment. Kinematics of plastic flow and especially, range of deformation region allows to predict stresses distribution on contact surface between the die, container and the extruded material.